Assesment of the Impact of Road Traffic on Air Pollution - Daniela Durcanska; Milan Moravcik (Communications - Scientific letters of the University of Zilina, 2003)
The negative impact of traffic on air pollution is a generally known fact. Automobile traffic has a great share in polluting the ground layer of the atmosphere where life develops and this applies especially to emissions, i. e. concentrations of polluting substances being emitted. This is the result of emissions of the main polluting substances produced by automobile traffic (CO – carbon monoxide, NOx – sum of nitrogen oxides and VOC – volatile organic compounds) just above the surface of the earth.The article deals with the influence of automobile traffic on air pollution using the methodology of calculating the volume of generated pollutants applied for this purpose.